PENGARUH LABA AKUNTANSI, TOTAL ARUS KAS, KOMPONEN ARUS KAS, RETURN ON EQUITY TERHADAP VOLUME PERDAGANGAN SAHAM PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2010-2013 - Riri Afrinta; Hardi -; Alfiati Silfi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The purpose of this study was to examine the effect of accounting earnings, total cash flow, operating cash flow, financing cash flow, investment cash flow and return on equity to the mining company's stock trading volume. The population in this study are all mining companies listed in Indonesia Stock Exchange (BEI) 2010-2013. Total population is about 16 mining companies. The sample in this study are all mining company listed on the Indonesia Stock Exchange (BEI) 2010-2013, the number of samples is as much as 16 mining companies. While the analysis of data using multiple regression models. Results of this study stated that the accounting profit, total cash flow, cash flow and return on equity investments have a significant impact on stock trading volume. While pperating cash flows and financing cash flow does not have a significant effect on stock trading volume.Keywords: Accounting, Cash, Return on equity, Stock Trading, and Mining